Disentangling competences: Interrelationships on creativity, innovation and entrepreneurship. (June 2015) - Edwards-Schachter, Mónica; García-Granero, Ana; Sánchez-Barrioluengo, Mabel; Quesada-Pineda, Henry; Amara, Nabil
Highlights: First study integrating creativity, innovation and entrepreneurship (CIE) as meta-competence. An analytical framework explaining CIE interrelationships is constructed. Implications to educating for, about and through entrepreneurship are analyzed. Empirical findings from an exploratory study on engineering students' perceptions are presented. Some implications for higher education are considered. Abstract: Creativity, innovation and entrepreneurship are recognized as crucial to foster an entrepreneurial culture, but their relationships from the competence-based approach are not yet sufficiently understood. This paper contributes to the ongoing debate on the nature of entrepreneurial competences critically analyzing the theoretical underpinnings to such interrelationships. Our literature review informs that the focus, core assumptions and educational approaches to entrepreneurial competences and the role of creativity and innovation may vary substantially depending on which educational paradigm is considered (educating 'for', 'about' and 'through' entrepreneurship). We present arguments on the adequacy of Social Cognitive Theory and Social Constructivism to explain the development of creativity, innovation and entrepreneurship (CIE) as a meta-competence. In this framework we undertake a preliminary empirical approximation to the area under study exploring how engineering students from two different socio-cultural contexts, Spain and USA, perceive CIE relationships and to what extent they believe they are developed by the education system. Empirical findings show that most students see themselves as creative people and consider that creativity is strongly related to innovation and entrepreneurship, being more convinced American than Spanish students on the relevance of creativity among entrepreneurs' competences. Moreover, their perceptions contrast with the role assigned to education, where they consider that creativity is still a pending subject in engineering education.